Description of the immature stages of the Neotropical whirligig beetle Gyrinus (Neogyrinus) rozei Ochs, 1953 (Coleoptera: Gyrinidae) and first report of the parasitoid wasp Melanosmicra sp. (Hymenoptera: Chalcididae) on a Gyrinus species - Colpani, Daniara; Benetti, César João; Hamada, Neusa; Andrade-Souza, Vanderly; Schoeninger, Karine; Michat, Mariano C. (Zootaxa, 2020)
In most species of Gyrinidae, the immature stages are unknown, especially due to the difficulty in collecting the juveniles and assigning them to a particular species. Molecular association is a feasible technique that may solve this problem. Recent studies have used DNA sequence data, specifically the gene cytochrome oxidase subunit I (COI), to associate immature and adult stages, thus enabling the description of the former. The objectives of this study were (1) to describe and illustrate the immature stages of Gyrinus (Neogyrinus) rozei Ochs, 1953 including morphometric, chaetotaxic and bionomic information, and (2) to assess the usefulness of the gene COI to associate immatures and adults of Gyrinus. The studied specimens were collected in Roraima state, northern Brazil. The association of immature and adult stages was done either by rearing adults under laboratory conditions or by using DNA sequence data (COI). Eggs were described based on scanning electron microscopy; they are distinguished mainly by several features of chorion, micropyle and reticulation. Larvae of G. (N.) rozei can be distinguished from those of other Neotropical Gyrinidae by a combination of several characters, including the stipes with five robust hook-like additional setae on the dorsointernal margin, and the lacinia roughly hook-shaped. The pupa is similar to that of G. argentinus Steinhel, 1869, except for the number of setae on the body. The first record of the parasitoid wasp Melanosmicra sp. (Hymenoptera: Chalcididae) on a Gyrinus species is also provided.